THE DIRECTIONS OF FORMATION OF MORAL QUALITIES IN THE REQUIREMENTS OF MODERN ERA - Mustafayev, Mushfig (Gênero & Direito, 2020)
The article has been investigated the dynamics and different aspects of moral qualities of student youth. This article is focused on the research of moral qualities in various investigations, and psychological mechanism of formation of moral qualities is explained .In the result of the research, it is determined that the formation of the values bears relative character , as well as it could go in the direction of positive and negative with the effect of situative factors. It became clear to us from this study, adequate self assessment of requirements create conditions to the positive strengthening of moral qualities. As well as, the attitude of students to the teaching, non-standard approach of moral qualities to the situation could play specific role in the progress of moral qualities.